Toward Low-Carbon Mobility: Examining the Influence of Green HRM and Work Engagement on Emission Reduction Through Green Innovation - Qodariah; Nugroho, Heru; Oktaviani, Retno Fuji; Lestari, Setyani Dwi; Richter, Ulf Henning (Universitas Brawijaya, Indonesia, 2025)
The transportation and motor vehicle sector in Indonesia is recorded as one of the sectors with the highest carbon emissions, which requires serious attention to reduce its negative impact on the environment. This study focuses on Green HRM and Green Work Engagement, two concepts that are increasingly popular in efforts to reduce the negative impact of the automotive industry on the environment. One factor that can be a link in improving environmental performance is Green Innovation. This study was conducted in several automotive industry companies with a large and unknown population; therefore, this study can use non-probability techniques, such as simple random sampling. Based on the online questionnaire distributed to 4 companies, a total of 320 questionnaires were distributed from October to December 2024. Of these, 236 respondents returned complete questionnaires, which can be used as research data. The research data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the research hypothesis. The results of the study show that Green HRM plays a significant role in increasing environmental awareness among employees of automotive industry companies; however, its influence on environmental performance and Green Innovation is not always substantial. Additionally, Green Work Engagement has been shown to have a significant impact on environmental performance. At the same time, Green Innovation serves as a mediator in the relationship between Green Work Engagement and improved environmental performance. However, Green Innovation cannot mediate the influence of Green HRM on environmental performance.